Contrasting responses of soil bacterial and fungal networks to photovoltaic power station - Li, Teng; Lu, Leilei; Kang, Ziqing; Li, Huijun; Wu, Jihua; Du, Weiguo (Frontiers in Microbiology, 2024)
The rapid expansion of solar photovoltaic (PV) power generation raises concerns regarding its impact on terrestrial ecosystems. Although the influence of PV panels on soil conditions and plant biomass is acknowledged, their effects on the assembly processes and co-occurrence networks of soil microbial communities remain understudied. Clarifying this influence is crucial for understanding the effects of photovoltaic panels on soil ecosystem functions. In this study, we first explored the effects of PV panels on soil properties. Then, using amplicon sequencing, we analyzed the impact of PV panels on soil microbial diversity and function, focusing specifically on the assembly processes and co-occurrence networks of bacterial and fungal communities. Our results indicate that the installation of PV panels improved soil conditions, leading to concurrent effects on microbial community structure and function. This process appears to be deterministic, driven primarily by homogeneous selection. Notably, PV panels increased the complexity of bacterial networks while decreasing their stability. In contrast, PV panels did not affect the complexity of fungal networks despite their stability increased. These findings provide new evidence that soil bacterial networks are more sensitive to PV panels installation than fungal networks, deepening our understanding of land-use change effects on soil ecosystem functions. Moreover, our study demonstrates that higher complexity does not necessarily mean higher stability at least in soil microbial systems, challenging the notion that ecological complexity favors their stability.